Molecular Signals of Heterogeneous Terrestrial Environments Identified in Dissolved Organic Matter: A Comparative Analysis of Orbitrap and Ion Cyclotron Resonance Mass Spectrometers - Simon, Carsten; Roth, Vanessa-Nina; Dittmar, Thorsten; Gleixner, Gerd (Frontiers in Earth Science, 2018)
Terrestrial dissolved organic matter (DOM) interlinks large carbon reservoirs of soils, sediments and marine environments but remains largely uncharacterized on the molecular level. Fourier Transform Mass Spectrometry (FTMS) has proven to be a powerful technique to reveal DOM chemodiversity and potential information encrypted therein. State-of the art FT-ICR MS (Ion Cyclotron Resonance) instruments are yet inaccessible for most researchers. To evaluate the performance of the most recent Orbitrap analyzer as a more accessible alternative, we compared our method to an established 15 Tesla FT-ICR MS on a diverse suite of 17 mainly terrestrial DOM samples regarding 1) ion abundance patterns, 2) differential effects of DOM type on information loss, and 3) derived biogeochemical information. We show that the Orbitrap provides similar information as FT-ICR MS, especially for compound masses below 400 m/z, and is mainly limited by its actual resolving power rather than its sensitivity. Ecosystems that are dominated by inputs of plant-derived material, like DOM from soil, bog, lake and rivers, showed remarkably low average mass to charge ratios, making them also suitable for Orbitrap measurements. The additional information gained from FT-ICR MS was highest in heteroatom-rich (N, S, P) samples from systems dominated by internal cycling, like DOM from groundwater and the deep sea. Here FT-ICR MS detected 37% more molecular formulae and 11% higher ion abundance. However, the overall information content, which was analyzed by multivariate statistical methods, was comparable for both data sets. Mass spectra-derived biogeochemical trends, for example the decrease of DOM aromaticity during the passage through terrestrial environments, were retrieved by both instruments. We demonstrate the growing potential of the Orbitrap as an alternative FTMS analyzer in the context of challenging analyses of DOM complexity, origin and fate.